Novelty Improves the Formation and Persistence of Memory in a Naturalistic School Scenario - Ramirez Butavand, D.; Hirsch, I.; Tomaiuolo, M.; Moncada, D.; Viola, H.; Ballarini, F. (Frontiers in Psychology, 2020)
One of the top challenges in education and neuroscience consists in translating laboratory results into strategies to improve learning and memory in teaching environments. In that sense, during the last two decades, researchers have discovered specific temporal windows around learning, during which the intervention with some experiences induces modulatory effects on the formation and/or persistence of memory. Based on these results, the aim of the present study was to design a specific strategy to improve the memory of students in a high-school scenario, by assessing the effect of a novel situation experienced close to learning. We found that the long-term memory about a geometrical figure was more precise in the group of students that faced a novel situation 1 h before or after learning the figure than the control group of students who did not face the novelty. This enhancement was probably triggered by processes acting on memory formation mechanisms that remained evident 45 days after learning, indicating that the improvement was sustained over time. In addition, our results showed that novelty no longer improved the memory if it was experienced 4 h before or after learning. However, far beyond this window of efficacy, when it was faced around 10 h after learning, the novel experience improved the memory persistence tested 7 days later. In summary, our findings characterized different temporal windows of the effectiveness of novelty acting on memory processing, providing a simple and inexpensive strategy that could be used to improve memory formation and persistence in high-school students.